Monitoramento temporal da cultura da soja através do sensoriamento remoto com a utilização de um RPA - Catani, Renan (2018)
The present research aims to evaluate the efficiency of the use of a RPA for the temporal monitoring of the soybean crop with low application cost, using the camera that is well-loaded in the equipment itself, and free-use software. To verify if farmers can use this technology to follow the development of their growing areas, efficiently, obtaining qualitative data through the interpretation of images collected by this equipment. It is concluded that the RPA is an efficient tool and easy operability which allows rural producers to better follow their areas, with a more comprehensive vision, which will help in decision making for better management.